Benchmarking visit of kumpulan inovatif dan kreatif (KIK) from the Faculty of Pharmacy, UiTM to the Institute of Medical Molecular Biotechnology (IMMB), Faculty of Medicine, UiTM Sungai Buloh campus - Aziz, Hamzah; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2025)
A delegation from Kumpulan Inovatif Dan Kreatif (KIK) of the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam, recently visited the Institute of Medical Molecular Biotechnology (IMMB), Faculty of Medicine, UiTM. The purpose of this benchmarking visit was to discuss the significance of the serological pipette, which has been selected as the featured product for this year's KIK competition.